Menilai Efektivitas Scrum dalam Manajemen Proyek Agile untuk Peningkatan Layanan Perusahaan - Damayanti, Murni (P3M Politeknik Negeri Banjarmasin, 2024)
Currently, various frameworks are used to implement Information Technology Governance (ITG). Due to the dynamic nature of ITG that is constantly evolving, there is an increasing demand for more efficient preparation, planning, and process development. In this context, having a supportive framework is a key priority. Therefore, the author intends to investigate how the integration of the ITIL framework into the Continual Service Improvement approach can enhance ITG. These efforts will be empowered by the implementation of a more adaptive and simplified operational approach in the form of Agile Project Management with the Scrum methodology. The goal is to accelerate the progress of ITG and make it more responsive and efficient in maximizing service quality across various organizations.